A Study on the role of Cambodia's trade policy in poverty reduction strategy - Vong, Donanya (KDI School, 2015)
The role of Cambodia’s trade policy is utmost advanced policy among government policies used to get target of accelerate country economy directly towards the effectiveness of encourage Cambodia integrate into the world market and global trading systems. Therefore, the Royal Government of Cambodia recognizes trade policy reform is a crucial role in country which is can promoting economic growth and mainly reflected in economic development policies. Especially in reducing poverty that is always a main concept of royal government vision for the future country development. In particular, to increase trade promoted by liberalization is a crucial role for assists growth by opens trade regions as well as free trade market its will lead country economy to a higher levels of growth specially in poverty reduction strategy of royal government. In order to reduce poverty, the types of solution to pursue should be based on clearly demonstrable links between several kind of role of trade policy and other related issue impact on the poor. However, the paper aims to do research and study on the role of trade policy reform based on performance of trade sector such as job creation, export promotion, free trade, etc, that can raising income of people and also have an effects on poverty reduction strategy in Cambodia.
Thesis(Master) --KDI School:Master of Public Policy,2015